Expanding the Knowledge Base: A Rejoinder to Townsend (1998) - Brian O. Brent (Journal of Research in Rural Education, 1998)
Perhaps the most common way to reply to a comment on one's article is to claim that the critic misunderstood the initial argument and is lost in the conceptual thicket. Such an approach would be inappropriate in this instance. Townsend's (1998) comments are not only thoughtful and instructive, but they support my view that policymakers should consider seriously the use of nonresidential expanded tax base approaches to fund public school systems. Thus, I will use this space to address, rather than dismiss, Townsend's concerns. I am hopeful that our exchange will benefit future analyses